Effect of peritoneal dialysis fluid containing osmo-metabolic agents on human endothelial cells - Bonomini M; Di Silvestre S; Di Tomo P; Di Pietro N; Mandatori D; Di Liberato L; Sirolli V; Chiarelli F; Indiveri C; Pandolfi A; Arduini A (Dove Medical Press, 2016)
Mario Bonomini,1,2 Sara Di Silvestre,3,4 Pamela Di Tomo,3,4 Natalia Di Pietro,2,4 Domitilla Mandatori,3,4 Lorenzo Di Liberato,1 Vittorio Sirolli,1,2 Francesco Chiarelli,2,4 Cesare Indiveri,5 Assunta Pandolfi,3,4 Arduino Arduini6 1Unit of Nephrology and Dialysis, 2Department of Medicine and Aging Sciences, 3Department of Medical, Oral and Biotechnological Sciences, 4Aging Research Center and Translational Medicine, CeSI-MeT, University “G. d’Annunzio”, Chieti-Pescara, 5Department DiBEST (Biologia, Ecologia, Scienze della Terra), Unit of Biochemistry and Molecular Biotechnology, University of Calabria, Arcavacata di Rende CS, Italy; 6CoreQuest, Manno, Switzerland Background: The use of glucose as the only osmotic agent in peritoneal dialysis (PD) solutions (PDSs) is believed to exert local (peritoneal) and systemic detrimental actions, particularly in diabetic PD patients. To improve peritoneal biocompatibility, we have developed more biocompatible PDSs containing xylitol and carnitine along with significantly less amounts of glucose and have tested them in cultured Human Vein Endothelial Cells (HUVECs) obtained from the umbilical cords of healthy (C) and gestational diabetic (GD) mothers. Methods: Primary C- and GD-HUVECs were treated for 72 hours with our PDSs (xylitol 0.7% and 1.5%, whereas carnitine and glucose were fixed at 0.02% and 0.5%, respectively) and two glucose-based PDSs (glucose 1.36% or 2.27%). We examined their effects on endothelial cell proliferation (cell count), viability (3-(4,5-dimethylthiazolyl-2)-2,5-diphenyltetrazolium bromide assay), intracellular nitro-oxidative stress (peroxynitrite levels), Vascular Cell Adhesion Molecule-1 and Intercellular Adhesion Molecule-1 membrane exposure (flow cytometry), and HUVEC-monocyte interactions (U937 adhesion assay). Results: Compared to glucose-based PDSs, our in vitro studies demonstrated that the tested PDSs did not change the proliferative potential both in C- and GD-HUVECs. Moreover, our PDSs significantly improved endothelial cell viability, compared to glucose-based PDSs and basal condition. Notably, glucose-based PDSs significantly increased the intracellular peroxynitrite levels, Vascular Cell Adhesion Molecule-1 and Intercellular Adhesion Molecule-1 membrane exposure, and endothelial cell–monocyte interactions in both C- and GD-HUVECs, as compared with our experimental PDSs. Conclusion: Present results show that in control and diabetic human endothelial cell models, xylitol–carnitine-based PDSs do not cause cytotoxicity, nitro-oxidative stress, and inflammation as caused by hypertonic glucose-based PDSs. Since xylitol and carnitine are also known to favorably affect glucose homeostasis, these findings suggest that our PDSs may represent a desirable hypertonic solution even for diabetic patients in PD. Keywords: carnitine, peritoneal dialysis solution, inflammation, nitro-oxidative stress, endothelial cells, xylitol